Exploration on the Effects and Molecular Mechanisms of Pterostilbene on Esophageal Cancer Based on Network Pharmacology - Liu, Guanglin; Yan, Xiaolong; Jiang, Jialing (Journal of Contemporary Medical Practice, 2024)
This study used a network pharmacology approach to analyze the potential role of Pterostilbene (PTS) in esophageal squamous cell carcinoma (ESCC). Compared with traditional ESCC treatments, which often have single targets, limited efficacy, and significant side effects, PTS, as a natural flavonoid compound, offers multiple targets, pathways, strong bioavailability, and blood-brain barrier penetration. These properties may compensate for the shortcomings of conventional drugs. The study constructed the PTS target network and PPI network, systematically analyzing its core targets and related pathways, providing a theoretical foundation for the development of PTS as a new drug for the prevention and treatment of ESCC.